The Death of Rotted Barley - Perry, Charles (Petits Propos Culinaires, 2012)
The medieval Arabs made a kind of soy sauce by culturing barley dough. To judge by the terminology, a mixture of Persian, Greek and Aramaic, it must have arisen in the Fertile Crescent. The mould-cultured barley was called either b?dhaj (Middle Persian p?dag, ‘rotted’) or qamn (Aramaic q?ml?, ‘mould’) and the soy sauce extracted from it was murr? (Greek halmyris, ‘something salty’). There’s no evidence of murr? in Iran or Byzantium, but it was popular throughout the Arab world during the Middle Ages. Iraq and North Africa had their own recipes and knew each other’s. (The North African recipe contained more spices; all murr? was spiced, at least with fennel and nigella.) There are a number of recipes in Arabic cookery books from the tenth and thirteenth centuries. It has entirely disappeared today. The question is, when did rotted barley die?